An Sistem Informasi Pengelolaan Aset di BPJS Ketenagakerjaan Wilayah Sumbagsel Menggunakan Metode Waterfall Berbasis Android - Pratiwi Amalia; Herlambang Saputra; Hidayati Ami (Jurnal Teknologi Informatika Multimedia Digital, 2025)
This research focuses on creating an asset management information system at BPJS Ketenagakerjaan Sumbagsel Region where asset management, especially electronic goods, is done manually using Google Sheets, data access is limited by certain staff so that the process is inefficient and less flexible if asset data is needed quickly. The purpose of this research is to develop an asset management information system at BPJS Ketenagakerjaan Sumbagsel Region based on Android that is feasible to implement and use. This research uses quantitative methods and Waterfall system development methods using UML (Unified Modeling Language). This system was built with the Flutter framework for Android applications, Laravel for websites and MySQL as a database. The results of the study produced an Android-based asset management information system and an asset dashboard website , which has been tested using Black Box and proven to function according to the designed features. This system allows barcode scanning, updating asset conditions, adding assets, moving assets, procuring assets and printing reports. Based on the results of a questionnaire to experts, this system received an assessment with an average of 74.28% in the “Agree” category, stating that the system built is useful in facilitating work, has an attractive visual appearance, is suitable for recommendation, increases work effectiveness and efficiency and is suitable for use in the BPJS Employment Office environment in the Sumbagsel Region in asset management.